Microplastics: Features of appearance, identification methods (subject review) - D. M. Myalenko (Пищевые системы, 2024)
Polymer packaging materials have become firmly embedded in our way of life. They are used in the manufacture of household items, as well as in the pharmaceutical, chemical, and automotive industries. Production and application of polymer packaging are expanding rapidly encompassing various spheres of the industry. According to Plastics Europe Market Research Group (PEMRG), global plastics production reached 348 million tons in 2017 and is likely to reach 33 billion tons by 2050. At the same time, about 26 million tons of plastic waste are generated annually on the territory of the European Union (EU), of which only 30% is collected for recycling. Despite this, in many countries of the world, including Russia, more than 50% of polymer materials are disposed of at landfills, where under the influence of external environmental factors (temperature, humidity), their destruction occurs with the formation of huge quantities of micro- and nanoplastics. Most people do not consider the environmental problems associated with microplastics to be serious. However, many studies aimed at in-depth study of this problem have proved that micro- and nanoplastics have significant negative effects on terrestrial and marine animals, as well as on human health, whether directly or indirectly. The identification of microplastics in various model environments and living systems is usually based on the use of infrared spectroscopy and Raman spectrophotometry. Each of the methods has its advantages and disadvantages, mainly related to sample preparation to improve the accuracy of identification. This review is devoted to the problem of formation and identification of microplastics in various natural objects.